2013
DOI: 10.1016/j.euroneuro.2012.11.012
|View full text |Cite
|
Sign up to set email alerts
|

European, randomized, phase 3 study of lisdexamfetamine dimesylate in children and adolescents with attention-deficit/hyperactivity disorder

Abstract: This study evaluated the efficacy and safety of lisdexamfetamine dimesylate (LDX) compared with placebo in children and adolescents with attention-deficit/hyperactivity disorder (ADHD) in Europe. Osmotic-release oral system methylphenidate (OROS-MPH) was included as a reference arm. Patients (6-17 years old) with a baseline ADHD Rating Scale version IV (ADHD-RS-IV) total score ≥ 28 were randomized (1:1:1) to dose-optimized LDX (30, 50, or 70 mg/day), OROS-MPH (18, 36, or 54 mg/day) or placebo for 7 weeks. Prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
138
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(162 citation statements)
references
References 17 publications
17
138
1
6
Order By: Relevance
“…Six studies reported ATX as having a lower risk of all-cause withdrawal than placebo, in contrast to the other nine trials comparing these treatments 27,[49][50][51][52][53] . Two studies reported placebo as having a higher risk of withdrawal than LDX 17,19 , and one study reported placebo as having a lower risk of withdrawal than LDX 18 . When analyzing all-cause withdrawals, it is important to consider that heterogeneity can be inevitable due to study design and protocol requirements; for example, rules for withdrawal due to lack of efficacy or tolerability can differ from trial to trial, and some trials may have follow-on trials allowing patients to 'drop out' into an open-label follow-on study.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Six studies reported ATX as having a lower risk of all-cause withdrawal than placebo, in contrast to the other nine trials comparing these treatments 27,[49][50][51][52][53] . Two studies reported placebo as having a higher risk of withdrawal than LDX 17,19 , and one study reported placebo as having a lower risk of withdrawal than LDX 18 . When analyzing all-cause withdrawals, it is important to consider that heterogeneity can be inevitable due to study design and protocol requirements; for example, rules for withdrawal due to lack of efficacy or tolerability can differ from trial to trial, and some trials may have follow-on trials allowing patients to 'drop out' into an open-label follow-on study.…”
Section: Discussionmentioning
confidence: 96%
“…Of the 32 included trials, 20 trials contributed to analyses for the CGI-I endpoint, of which 15 used the CGI-I definition and 5 used the CGI-ADHD-S definition; 16 trials contributed to analyses for the ADHD-RS endpoint, of which 12 used the ADHD-RS 25% reduction definition, 2 used a 40% reduction, 1 used a 20% reduction, and 1 used a 30% reduction; 28 trials contributed to analyses for the all-cause withdrawal endpoint; and 27 trials contributed to analyses for the adverse event withdrawal endpoint. We found only one trial reporting DEX as part of the literature searches, but this was excluded due to the crossover study design [17][18][19]27, .…”
Section: Evidence Basementioning
confidence: 99%
See 1 more Smart Citation
“…A recent phase III study in children and adolescents (6 to 17 years) with ADHD from 10 European countries included long-acting, osmotic-release oral system methylphenidate (OROS-MPH) as an active reference arm to provide validation of the study design 38 .…”
Section: Efficacymentioning
confidence: 99%
“…3 Conversely, some researchers have argued that stimulants may actually improve a child's sleep, noting that these medications are generally well tolerated and are effective in reducing the core symptoms of ADHD, and these positive effects may generalize to sleep problems as well. 5,6 Sleep problems are common for youth with ADHD even when they are not taking medications, 7 and some clinicians claim that children with ADHD sleep better when taking medications. 8 Stein et al 9 explained that difficulties falling asleep commonly observed in children with ADHD may be due to a "rebound effect" in which the child experiences withdrawal symptoms as the medication wears off near bedtime, suggesting that there may be benefits to maintaining active stimulants in the child's body even in the hours approaching bedtime.…”
mentioning
confidence: 99%